PERSEPSI SISWA TERHADAP PEMANFAATAN LABORATORIUM VIRTUAL DALAM PEMBELAJARAN FISIKA TOPIK GERAK LURUS (SURVEY TERHADAP SISWA KELAS X SMAN 87 JAKARTA SELATAN - Heni Safitri; Herawati (Jurnal Pendidikan, 2011)
Experiment is the core of physics subject. Most of physics phenomena taught in school, are not based on observation. They are taught verbally and in few cases they are correlated with phenomena found in daily life. The presence of virtual laboratory could solve the problems as well as provide alternative solution for lack of equipments of physics laboratory in most schools. This research explained the perception of students about utilization of virtual laboratory in physics to learn the topic of linear motion. The research carried out on student class X in SMAN 87 Jakarta Selatan in 2009/2010. Data is collected from quesioner and then analyzed descriptively. The result indicates that using virtual laboratory, students better understand the concept of linear motion and give them experience of more save and more compartable practicum.